Relationship between language proficiency and growth during reading interventions. Issue 6 (2nd November 2017) - Burns, Matthew K.; Frederick, Amy; Helman, Lori; Pulles, Sandra M.; McComas, Jennifer J.; Aguilar, Lisa
ABSTRACT: Many English language learners (ELLs) experience difficulties with basic English reading due in part to low language proficiency. The authors examined the relationship between English language proficiency and growth during reading interventions for ELLs. A total of 201 second- and third-grade students with a variety of home languages participated. The students were identified as needing a targeted intervention, because scores on the fall oral reading fluency screening measure fell below the benchmark criterion. Thus, all participating students received reading interventions approximately four times each week throughout the school year. Results indicated that those students identified in the lowest English proficiency stage on the Assessing Comprehension and Communication in English State-to-State (ACCESS) made the highest growth as indicated in the spring benchmark assessment, and the ACCESS score added negligible variance beyond baseline reading skills. Implications for practice and research are discussed.